Analysis of RNA Interference Lines Identifies New Functions of Maternally-Expressed Genes Involved in Embryonic Patterning in Drosophila melanogaster. - Liu, N.; Lasko, P. (G3 : genes - genomes - genetics, 2015)
Embryonic patterning in Drosophila melanogaster is initially established through the activity of a number of maternally expressed genes that are expressed during oogenesis. mRNAs from some of these genes accumulate in the posterior pole plasm of the oocyte and early embryo and localize further into RNA islands, which are transient ring-like structures that form around the nuclei of future primordial germ cells (pole cells) at stage 3 of embryogenesis. As mRNAs from several genes with known functions in anterior-posterior patterning and/or germ cell specification accumulate in RNA islands, we hypothesized that some other mRNAs that localize in this manner might also function in these developmental processes. To test this, we investigated the developmental functions of 51 genes whose mRNAs accumulate in RNA islands by abrogating their activity in the female germline using RNA interference. This analysis revealed requirements for ttk, pbl, Hip14, eIF5, eIF4G, and CG9977 for progression through early oogenesis. We observed dorsal appendage defects in a proportion of eggs produced by females expressing double-stranded RNA targeting Mkrn1 or jvl, implicating these two genes in dorsal-ventral patterning. In addition, posterior patterning defects and a reduction in pole cell number were seen in the progeny of Mkrn1 females. Because the mammalian ortholog of Mkrn1 acts as an E3 ubiquitin ligase, these results suggest an additional link between protein ubiquitination and pole plasm activity.